Evaluation of Physical Activity and its Effective Factors in Junior High School Female Students in Rafsanjan City: Application of Social-cognitive Theory, 2017-18 - Zahra Soleiman Ahari (Qom University of Medical Sciences, 2021)
Background and Objectives: The World Health Organization (WHO) introduces appropriate physical inactivity among the 5 main causes of obesity and overweight. This study aimed to identify the determinants of physical activity among female students based on Social Cognitive Theory (SCT). Methods:  A descriptive cross-sectional study was conducted among 640 female junior high school students in Rafsanjan City, Iran. The study sample was selected by cluster random sampling approach. The data collection tool was a three-part questionnaire for demographic information, physical activity behavior assessment, and its determinants based on SCT. The collected data were analyzed by SPSS using the Mann-Whitney U test, Kruskal-Wallis test, Spearman correlation, and multivariate regression analysis at a significant level of 0.05. Results: The mean score of physical activity time was 79.28 (min/week) in the study participants. Except for environmental factors, the explore studentschr('39') level of physical activity presented a statistically significant relationship with other constructs of SCT, higher level of parental education, lower body mass index, and membership in sports teams. The multivariate regression analysis data suggested social reinforcement as the strongest predictor of physical activity (P=0.004, β=0.129). Conclusion: The rate of physical activity of 95.8 female students was less than the WHO’s recommendation (60 minutes per day). Therefore, it is recommended to design, implement, and evaluate interventional programs at the social level.